Kebijakan Hukum Pidana Terhadap Pengaturan Pelanggaran Batas Kecepatan Kendaraan Bermotor Dan Penegakan Hukumnya(Studi Kasus Di Satlantas Polres Wonogiri) - Hidayat, Herlambang Tony (2017)
The purpose of this study was to analyze the criminal law policy on violation of motor vehicle speed limits and its law enforcement. This is an empirical legal research. It was conducted at The Traffic Police Command in Wonogiri District. It uses primary data as the data source with qualitative analysis technique. The results showed that: the criminal law policy is imposing sanctions against violation of speed limits as some deterrence. Meanwhile the law enforcement in the form of punishment against violators of speed limits is not enforced by the traffic police. The Hurdles in law enforcement of speed limits violation: (1) Society lacks knowledge of speed limits rule; (2) There are no speed limits detection device; (3) The increasing number of motor vehicles is complicating the police to enforce the speed limit rules.